1985
DOI: 10.1095/biolreprod33.1.247
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of protein hormones on cultured rabbit ovarian surface epithelial cells

Abstract: Throughout life, the ovarian surface epithelium (OSE) undergoes morphogenetic changes that may be hormonally regulated. To investigate this possibility, a population of cells morphologically identical to native OSE cells was isolated from estrous rabbits with collagenase, unit gravity sedimentation, and trypsin-EDTA. Cells were incubated with various concentrations of protein hormones in serum-rich medium or in a chemically defined medium containing fibronectin. Tritiated thymidine was added 24 h before interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Several studies have demonstrated that certain OSE cancer cell lines undergo enhanced cellular proliferation following LH addition (Casagrande et al 1979, Simon et al 1983, Osterholzer et al 1985, Syed et al 2001, Parrott et al 2001b. Controversy, however, exists whether LH has an influence on the proliferative activity of all OSE cells, as also decreased (Zheng et al 2000, Tourgeman et al 2002 or unchanged (Ala-Fossi et al 1999, Ivarsson et al 2001, Wright et al 2002 OSE cell proliferation in response to LH have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that certain OSE cancer cell lines undergo enhanced cellular proliferation following LH addition (Casagrande et al 1979, Simon et al 1983, Osterholzer et al 1985, Syed et al 2001, Parrott et al 2001b. Controversy, however, exists whether LH has an influence on the proliferative activity of all OSE cells, as also decreased (Zheng et al 2000, Tourgeman et al 2002 or unchanged (Ala-Fossi et al 1999, Ivarsson et al 2001, Wright et al 2002 OSE cell proliferation in response to LH have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of LH receptors (LH-Rs) has been demonstrated in normal OSE cells (Parrott et al 2001a), in epithelial cells lining ovarian inclusion cysts (Kuroda et al 1998) and in approximately 50% of ovarian carcinomas (Mandai et al 1997). However, controversy exists as to whether there is a direct effect of LH on OSE cell survival, as increased (Casagrande et al 1979, Simon et al 1983, Osterholzer et al 1985, Syed et al 2001, Parrott et al 2001a), unchanged (Ala-Fossi et al 1999, Ivarsson et al 2001, Wright et al 2002 as well as decreased (Zheng et al 2000, Tourgeman et al 2002 proliferation rates in response to LH have been reported. Many OSE tumors have been shown to contain low apoptotic indices and, therefore, it may be possible that LH influences OSE tumor growth and survival through inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Most in vivo studies have explored the proliferative activity of the OSE at the follicle apex, in relation to ovulation wound repair (Osterholzer et al 1985, Beller et al 1995, or after gonadotropin stimulation (Beller et al 1995, Davies et al 1999, Stewart et al 2004. However, the proliferative activity of the OSE throughout the estrous cycle has received little attention, and a comprehensive view of the cyclic changes in the OSE is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, gonadotropins activate intraovarian carcinogenic enzymes and stimulate or inhibit HOSE growth. [22][23][24][25] A link between ovulation and HOSE cancer is suggested by experimental, epidemiologic, and clinical studies. 25,26 Although the hypothesis remains controversial, some investigators believe that exogenous hormones, especially estrogens, may play a pathogenetic role in HOSE carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%